Fruit and Vegetable Consumption and Risk of Esophageal Cancer: A Case-Control Study in North-West China - Tang, Li; Lee, Andy; Xu, F.; Zhang, T.; Lei, J.; Binns, Colin (Wiley-Blackwell Publishing, Inc., 2014)
The north-western region of China carries a big burden of esophageal cancer with incidence above the national average. This study ascertained the association between fruit and vegetable consumption and the risk of esophageal cancer in this remote part of China. A case-control study was undertaken in Urumqi and Shihezi, Xinjiang Uyghur Autonomous Region of China, between 2008 and 2009. Participants were 359 incident esophageal cancer patients and 380 hospital-based controls. Information on habitual fruit and vegetable consumption was obtained by face-to-face interview using a validated semiquantitative food frequency questionnaire. Unconditional logistic regression analyses were performed to assess the strength of the associations. The esophageal cancer patients consumed significantly less fruits (mean 364.3, standard deviation [SD] 497.4 g) and vegetables (mean 711.4, SD 727.9 g) daily than their counterparts without the disease (mean 496.5, SD 634.4 g and mean 894.5, SD746.1 g, respectively). The adjusted odds ratios were 0.48 (95% confidence interval 0.33–0.71) and 0.46 (95% confidence interval 0.32–0.68) for consuming at least 515 g of fruits and 940 g of vegetables per day, respectively, relative to at most 170 g and 520 g. With respect to nutrients contained in fruits and vegetables, intakes of vitamin C, vitamin E, ß-cryptoxanthin, potassium, and magnesium at high levels also reduced the esophageal cancer risk. In conclusion, inverse associations were evident between consumption of fruits and vegetables and the risk of esophageal cancer for adults residing in north-west China.